The effectiveness of using photomath in improving mathematics learning outcomes and learning interest among grade students - Eric Riskianto Saputra; Dimas Anditha Cahyo Sujiwo; Indah Rahayu Panglipur (Hipotenusa Journal of Research Mathematics Education (HJRME), 2026)
Mathematics is a subject that plays a crucial role in developing logical and analytical thinking skills. However, students’ learning outcomes and interest in mathematics remain relatively low. One approach to address this issue is to utilize educational technology, such as the Photomath app. This study aims to determine the effectiveness of using the Photomath app on students’ learning outcomes and interest in mathematics. The study employed a quantitative approach with a quasi-experimental design of the nonequivalent control group type, involving three groups: an experimental group, a combination group, and a control group. The research instruments consisted of a learning outcomes test and a learning interest questionnaire. Data were analyzed using One-Way ANOVA, Tukey’s Post Hoc test, and MANOVA. The results showed that there was a significant difference in mathematics learning outcomes among the groups based on the One-Way ANOVA test (F(2,87) = 30.157; p < 0.001). The Tukey test results indicated that the experimental group had significantly higher learning outcomes compared to the other groups. Furthermore, the MANOVA results indicate that the use of Photomath simultaneously influences both students’ learning outcomes and their interest in learning. Thus, the Photomath app is effective as a learning medium for improving students’ mathematics learning outcomes and interest in learning. Future research is recommended to include other variables, different educational levels, and a longer treatment duration to obtain more comprehensive findings